Development of Thinking Skills in Early Childhood - Siti Aisyah (International Journal of Emerging Issues in Early Childhood Education, 2019)
This research aims to obtain empirical data on the effect of reading method and thinking skills toward intelligence language of early childhood. Thus the researchers wanted to investigate the causal relationship between the reading method and thinking skills with the intelligence language of children by giving treatment to the experimental group and compared it with the control group. This study used a treatment design by level 2 x 2 be In the design, each of the independent variables are classified into two sides, includes action variable that is reading methods (A) are classified into the Big Book Methods (A1) and Syllables Method (A2). Whereas moderator variables that is thinking skills (B), are classified based on high and low level into high-level thinking skills (B1) and low-level thinking skills (B2). ANOVA calculation results showed that language skills of children who followed reading activities by using the Big Book method is higher than the language skills of children who attend reading activities by using Syllables method. Thus, there is the effect of the application of the Big Book method and Syllables methods toward language skills of children.